Directions of Development of Human Capital of Innovative Petrochemical Enterprises - I. Shinkevich, Alexey (2020)
The main aim of the article is to identify the directions of innovative human capital development of industrial enterprises based on the development of an improved assessment methodology. The object of the research is industrial enterprises of the Russian economy. The subject of the research is innovative activity of the enterprises. The key research method is modeling (building a regression model, production function), which makes it possible to systematically study the links between indicators of enterprise innovation and the use of human capital in this process, as well as identify problem areas and directions of human capital development of industrial enterprises.